Letter : Position of Spanish seamen - Hallsworth, Joseph
025a-0114-001 Telephone Rusholme 2804-8 (five lines) Telegrams "Nudawn" Phone Manchester Money orders to be made payable at Manchester Reg Trade union no 1798T Approved Society for National Health Insurance No 296 National Union of Distributive and Allied Workers Affiliated to the BRITISH AND SCOTTISH TRADES UNION CONGRESSES LABOUR PARTY INTERNATIONAL CLOTHING WORKERS FEDERATION INTERNATIONAL TRANSPORT WORKERS FEDERATION INTERNATIONAL FEDERATION of COMMERCIAL CLERICAL AND TECHNICAL EMPLOYEES INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONAL FEDERATION OF GENERAL FACTORY WORKERS FOOD AND DRINK TRADES INTERNATIONAL FEDERATION J. Hallsworth W.A. Robinson General Secretaries Registered Office Oakley Wilmslow Road, Fallowfield Manchester, 14. IN REPLYING PLEASE QUOTE 8634/RAC/DB 4th April 1939 Mr. H.V. Tewson, Assistant Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, Position of Spanish Seamen At a special meeting of our Executive Council held on Sunday last a report was submitted of the recent conference of representatives of Unions comprising the British Section of the International Transport Workers' Federation on the question of financial aid for Spanish trade unionist crews at present in British ports. The Executive agreed to adopt the recommendation carried by the conference and to pay the quota of £40. 0. 0 due from this organisation as a further instalment to the International Solidarity Fund on behalf of Spanish trade unionists. A cheque is sent herewith and I shall be glad to have your receipt in due course worded as follows so as to keep the payment in conformity with the rules of this Union :- As a contribution in aid of the Spanish Trade Union Movement. Yours sincerely, J Hallsworth Industrial General Secretary Enclosure 292/946/25a/114